Novedades y nuevas citas de musgos (Bryophyta) de la Reserva Natural Punta Lara (Buenos Aires, Argentina) - Valdés, Fabricio Emanuel (2021)
Background and aims: A list of mosses recorded in Punta Lara Natural Reserve (Buenos Aires, Argentina) is presented, increasing the knowledge of the diversity and distribution of mosses in the country. M&M: The specimens were collected and identified according to conventional taxonomic criteria and deposited in the Herbarium of the Spegazzini Institute (LPS). Global Biodiversity Information Facility (GBIF) records were consulted as a source of information about the species distribution. Results: Fifteen species of mosses distributed in 11 families were identified in Punta Lara Natural Reserve. The genus Thamnomalia Olsson, Enroth & Quandt, represented by Thamnomalia glabella (Hedw.) Olsson, Enroth & Quandt and the species Sematophyllum adnatum (Michx.) E. Britton are recorded for the first time for Argentina. Discussion and Conclusions: Two species are new records for Argentina and 11 species are recorded for the first time for Buenos Aires province. Several species are tropical, extending their distribution towards temperate regions.